Pengaruh Pelaksanaan Supervisi Akademik terhadap Kualias Kinerja Guru di SMP Negeri 2 Sangatta Utara - Irma, Irma; Ramdanil Mubarok; H. Muhammad Imam Syafi (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
The purpose of this study was to determine how much academic supervision at SMP Negeri 2 Sangatta Utara improves teacher performance. This study, which used a quantitative methodology and a straightforward linear regression analytic method, included all 41 of the school's teachers. Direct observation, the distribution of questionnaires, and documentation were used to gather data. The SPSS program was used to first assess the validity and reliability of each instrument. Descriptive statistics, linear regression testing to determine the association between variables, and normality and linearity tests were all part of the data analysis. With a significance value of 0.000 and a t-value of 4.299 that was higher than the t table of 2.021, the study's findings demonstrated a statistically significant association between academic supervision and the caliber of teacher performance. Furthermore, the use of academic supervision accounts for 51.1% of the difference in teacher performance, with other factors not included in this study influencing the remaining 48.9%. These results suggest that while academic supervision is a significant component in raising the caliber of teacher work, other outside variables still require consideration in order to achieve the best possible outcomes during the teaching process.